Phenotypic whole-cell screening identifies a protective carbohydrate epitope on Klebsiella pneumoniae. Issue 5 (27th May 2022) - Berry, Sophia; Caceres, Carolina; Rust, Steven; Minter, Ralph; Grant, Andrew
Abstract : The increasing occurrence of recalcitrant multi-drug resistant (MDR) Klebsiella pneumoniae infections coupled with a diminishing pipeline of new antibioticswarrants the investigation of alternative antimicrobial therapies. We employed a target-agnostic phage display approach using live K. pneumoniaebacteria with the aim of isolating therapeutic monoclonal antibodies (mAbs) targetingconserved epitopes among clinically relevant strains. mAb targets were explored using ELISA and biolayer interferometry, and a high-throughput opsonophagocytic killing assay was developed to determine functional activity. Fluorescence-activated cell sorting was used to screen a global panel of clinical isolates, and high-content imaging further explored binding and functional activity. One mAb was tested in vivousing a lethal murine model of pneumonia. mAbs binding to carbohydrate epitopes were isolated in phage display selections enriched on wild-type and capsule-deficient strains. mAbs binding O1 lipopolysaccharide (LPS) and cross-binding O1/O2 LPS were identified. mAbs were shown to promote opsonophagocytic killing by human monocyte-derived macrophages, and clearance of macrophage-associated bacteria. One mAb, named B39, protected mice against MDR O1 and O2 strains when dosed therapeutically in a murine pneumonia model. Binding to a panel of O1 and O2 clinical isolates suggests B39 binds to both d -galactan-I and d -galactan-II of the LPS. With the rise of antimicrobial resistance among enteric pathogens, the discovery of a novel therapeutic mAb targeting the most prevalent K. pneumoniaeserotypes demonstrates a significant advancement in the field, and showcases the potential of alternative antimicrobial therapies for the treatment of MDR infections.